Sliding of Elastically Similar Complete Contacts - Rozibab, Mohd. Kamalmursyid (Universiti Teknologi Petronas, 2009)
Sliding of a square block on an elastically similar plane is going to be analyzed. The stresses present at the edge of complete contacts have high concentration and need to be studied. The analysis will be carried out using Finite Element Analysis (FEA) software, ANSYS. Simulation of the sliding contact will be executed and the parameters of the contact analysis such as contact pressure, contact frictional stress, normal stress and shear stress will be obtained. In addition, the region or location of the contact interface having highest values of those parameters will be determined and the factors affecting those parameters are also determined.